Towards high‐efficiency multi‐junction solar cells with biologically inspired nanosurfaces. (2nd August 2012) - Yu, Peichen; Chiu, Meng‐Yih; Chang, Chia‐Hua; Hong, Chung‐Yu; Tsai, Yu‐Lin; Han, Hau‐Vei; Wu, Yu‐Rue
ABSTRACT Multi‐junction solar cells offer extremely high power conversion efficiency with minimal semiconductor material usage, and hence are promising for large‐scale electricity generation. However, suppressing optical reflection in the UV regime is particularly challenging due to the lack of adequate dielectric materials. In this work, bio‐inspired antireflective structures are demonstrated on a monolithically grown Ga0.5In0.5P/In0.01Ga0.99As/Ge triple‐junction solar cell, which overcome the limited optical response of reference devices. The fabricated device also exhibits omni‐directional enhancement of photocurrent and power conversion efficiency, offering a viable solution to concentrated illumination with large angles of incidence. A comprehensive design scheme is further developed to tailor the reflectance spectrum for maximum photocurrent output of tandem cells. Copyright © 2012 John Wiley & Sons, Ltd.